Effect of acidic environment on slake durability of iron ore - An experimental approach - Singh T.N.; Madhusudhan N.; Monjezi M. (My University, 2025)
Forces of weathering and erosion reduce the strength of rocks leading to various types of failures in slopes and strata. The present paper deals with the variation in the strength of iron ore bearing rocks with the acidity of the solutions to which they are exposed. Slake durability index is a measure of the durability of the rock when exposed to a slaking fluid medium. The variations in the slake durability indices of iron ore samples were studied by exposing them to acidic solutions of different pH values. The results indicate that the slake durability of iron ore rocks decreases with increase in the acidity of the solutions to which they are exposed. This behaviour is attributed to combined forces of weathering and corrosion acting on iron ore in acidic slaking media.